Comparison of qSOFA Score Versus qSOFA + Serum Lactate Score for Prediction of Mortality in Patients with Intra-Abdominal Sepsis (Journal of BP Koirala Institute of Health Sciences, 2025)
Background: Abdominal sepsis leading to septic shock is a common surgical condition and leading cause of admission in the surgical intensive care unit (ICU). Lactate has been shown to predict adverse outcomes in patients with suspected infection along with quick sequential organ failure assessment (qSOFA) score. The study aimed to compare the predictive accuracy of the quick Sequential Organ Failure Assessment (qSOFA) score and lactate-enhanced qSOFA (LqSOFA) score for in-hospital mortality among patients presenting with intra-abdominal sepsis to the emergency department.Methods: A prospective comparative study was conducted at Kathmandu Medical College Teaching Hospital, Nepal, from January 1, 2023, to December 31, 2023. Patients with intra-abdominal infection presenting with features of sepsis or septic shock were included. After obtaining ethical clearance (reference number: 0403202006), data on qSOFA and LqSOFA scores were collected using a standardized proforma, and outcomes were recorded. Statistical analysis was performed using SPSS version 26. Continuous variables were compared using the Student’s t-test, categorical variables using the Chi-square test, and Receiver Operating Characteristic (ROC) curve analysis was performed to determine discriminative ability. Youden’s Index was used to identify the optimal cut-off value for mortality prediction.Results: A total of 114 patients who were diagnosed with intraabdominal sepsis meeting the inclusion criteria were analysed. The mortality rate was 22.8% (n=26). The LqSOFA score presented the most significant discrimination with an area under the receiver operating characteristic curve (AUROC) of 0.664 (95% CI: 0.53-0.79) higher than the AUROC of the qSOFA, AUROC 0.575 (95% CI: 0.43- 0.71). The addition of lactate threshold identified higher proportion of patients at risk of mortality.Conclusion: This study suggests that LqSOFA score is a better predictor of mortality than the qSOFA score alone in patients with intra-abdominal sepsis.